health relationship with social interaction in students at MTS Al-Istiqomah Pasarkemis - Devianita Raestiningsih (Jurnal Genta Kebidanan, 2021)
The lack of social interaction between students and peers, there were 18 students in the closed group, from a percentage calculation of 75.1% and there were 6 students who had an open attitude from a percentage value of 25.1%. That way, it really needs efforts in dealing with problems with openness of students to someone who, according to him, the person he really trusts can keep the secrets of his every expression. This study aims to determine the relationship between mental health and social interaction among students at MTS Al-Istiqomah Pasarkemis in 2020. This type of quantitative research is random sampling. The sample used in this study were 114 students. The data were analyzed using chi-square test and the results of the health statistical p value were 0.000. This shows that the p value on social interaction is p value 0.000 with r = 0.469, it can be concluded that there is a relationship between health and social interaction among students. Students should be able to interact well between peers and people who are older than him for health with social interactions, don't bully between peers at school because it can affect mental health and social interactions in the environment.